Socio‐demographic and structural barriers to being tested for chlamydia in general practice. Issue 3 (15th February 2016) - Lau, Andrew; Spark, Simone; Tomnay, Jane; Temple‐Smith, Meredith; Fairley, Christopher K; Guy, Rebecca J; Donovan, Basil; Hocking, Jane S
Abstract: Objectives: To investigate socio‐demographic and structural factors associated with not providing a specimen for chlamydia testing following a request by a general practitioner. Design, setting and participants: Cross‐sectional analysis of chlamydia testing data for men and women aged 16–29 years attending general practice clinics participating in a cluster randomised controlled trial evaluating the effectiveness of a chlamydia testing intervention. The study period was the 2013 calendar year. Outcome: The proportion of chlamydia test requests for which the patient did not provide a specimen for testing. Results: During the study period, there were 13 225 chlamydia test requests, for which a chlamydia test was not performed in 2545 instances (19.2%; 95% CI, 16.5–22.3%). Multivariate analysis indicated that the odds for not undertaking a requested test were higher for men (adjusted odds ratio [aOR], 1.4; 95% CI, 1.3–1.6), those aged 16–19 years (aOR, 1.3; 95% CI, 1.1–1.4), those living in areas of greater socio‐economic disadvantage (aOR, 1.2; 95% CI, 1.1–1.4 for each additional quintile of Index of Relative Socio‐economic Disadvantage), and those attending clinics without on‐site pathology collection (aOR, 1.4; 95% CI, 1.0–1.9). Conclusion: One in five young people did not submit a specimen for chlamydia testing despite their GP requesting it. This highlights the need for clinics to establish systems which ensure that men and those aged 16–19 years undertake chlamydia tests requested by a GP.